2005
DOI: 10.1002/cphc.200400293
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polarity on Coadsorbed Molecular Nanostructures of Substituted Phthalocyanine and Thiol Molecules

Abstract: One of the main goals of nanoscience and nanotechnology is the fabrication of nanodevices, using single atoms or molecules, by means of the bottom-up approach, which can overcome the limitations of traditional industrial methods (i.e., top-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…13). 42,88 It was shown that the type of central metal atom does not have much influence over the organization of Pcs on surfaces; still each metal appears with a different contrast according to its d z 2 orbital occupation. 89 Two-dimensional bifunctional structures with a 1 : 1 composition of F 16 PcCo and TPPNi (Ni(II) tetraphenylporphyrin) were obtained by vapour deposition in UHV onto Au (111).…”
Section: Nanostructures Observation Of Pc Nanostructures On Surfacesmentioning
confidence: 99%
“…13). 42,88 It was shown that the type of central metal atom does not have much influence over the organization of Pcs on surfaces; still each metal appears with a different contrast according to its d z 2 orbital occupation. 89 Two-dimensional bifunctional structures with a 1 : 1 composition of F 16 PcCo and TPPNi (Ni(II) tetraphenylporphyrin) were obtained by vapour deposition in UHV onto Au (111).…”
Section: Nanostructures Observation Of Pc Nanostructures On Surfacesmentioning
confidence: 99%
“…The technique has been used extensively in the areas of electrochemical sensors and biosensors [17][18][19], molecular electronic devices [20,21], and corrosion studies [22]. Fabrication of MPc molecular nanostructures and 2D self-assembled monolayers has begun to generate some interests [23,24]. This perhaps should not be surprising given that many of the potential applications of MPc complexes (such as in the development of nanostructured electronic, catalytic and sensing devices) will require their surface-confined ultrathin molecular films on surfaces.…”
Section: Introductionmentioning
confidence: 97%
“…Self-assembly is governed by the subtle balance between molecule-molecule and molecule-surface interactions, which can be tuned by modifying surrounding atoms of the phthalocyanine [18]. Experiments [19] showed that molecular films consisting in chlorine-zinc-phthalocyanine (ZnPcCl 8 ) molecules adsorbed onto Ag(1 1 1) surface, evolve in time towards a close-packed organization.…”
Section: Introductionmentioning
confidence: 98%